Progress in ovarian cancer diagnostics - Nowak-Markwitz, Ewa; Spaczyński, Marek (Menopause Review/Przegląd Menopauzalny, 2006)
Ovarian cancer is characterized by lack of early symptoms, presentation at an advanced stage, and poor prognosis. The molecular events leading to the development and progression of ovarian carcinoma are not completely understood. The only available biomarker is CA 125, which has an unacceptably low sensitivity and specificity for diagnostic use in screening and early detection. Many serum markers have been assessed alone and in combination with CA 125 in detecting ovarian cancer at an early stage. Some of the most promising are subjected to investigations leading, we hope, to improve the dismal survival rate. Tumor transcription profiling and serum proteomic profiling are one of the most promising new approaches for cancer diagnosis. Recent developing techniques are capable to assess of global gene expression to distinguish specific tumor type, histologic subtypes and different clinical outcome. The use of rapid, high throughput mass spectrometric-based fingerprints of proteins may prove to be valuable for early detection, molecular classification of tumors and in target therapy arrangement. These specificities and sensitivities are far superior to those obtained by using classical cancer biomarkers. But the new methods need to be thoroughly validated before clinical implementation is warranted.